Uncovering the pathways to gender equality and women’s empowerment through agricultural research for development: Lessons from the Feed the Future innovation labs - Eissler, Sarah; Bryan, Elizabeth; Magalhaes, Marilia (International Food Policy Research Institute, 2025)
Gender equality and women’s empowerment are important development goals for their intrinsic value as well as for achieving other important wellbeing outcomes, such as improved health, nutrition, and food security. Agricultural research for development plays an important role in understanding gender relations, dynamics, and inequalities and in identifying effective strategies and interventions to achieve these goals. The Feed the Future Innovation Labs (ILs) were initiatives supported by the United States Agency for International Development (USAID) and led by U.S. universities, in partnership with international and national research institutes, with the aim to achieve poverty reduction, food security, nutrition, and resilience objectives. The ILs also aimed to facilitate women’s empowerment and address gender inequality in agri-food systems (AFS).